Medieval and post-medieval archaeological heritage in Polish caves and the problems of its protection - Wojenka, Michał (Archaeologia Historica Polona, 2022)
This paper discusses cave use in Poland during medieval and post-medieval periods, focussing on the Cracow Upland in particular. The purpose is to try to provide a short overview of the medieval and post-medieval material culture in Polish caves through the lens of functions played by caves in historical periods (domestic occupation, workshopusage, storage, hideaways in times of unrest, use of caves for funeral purposes), and to indicate present-day threats to the archaeological records in our caves, relating mostly to the unprofessional speleological activities.